Use of a Clostridioides difficile Murine Immunization and Challenge Model to Evaluate Single and Combination Vaccine Adjuvants Consisting of Alum and NKT Cell-Activating Ligands - Lang, Gillian A.; Norman, Kaylee; Amadou Amani, Souwelimatou; Shadid, Tyler M.; Ballard, Jimmy D.; Lang, Mark L. (Frontiers in Immunology, 2022)
Adjuvant combinations may enhance or broaden the expression of immune responses to vaccine antigens. Information on whether established Alum type adjuvants can be combined with experimental CD1d ligand adjuvants is currently lacking. In this study, we used a murine Clostridioides difficile immunization and challenge model to evaluate Alum (AlhydrogelTM), α-galactosylceramide (α-GC), and one of its analogs 7DW8-5 singly and in combination as vaccine adjuvants. We observed that the Alum /α-GC combination caused modest enhancement of vaccine antigen-specific IgG1 and IgG2b responses, and a broadening to include IgG2c that did not significantly impact overall protection. Similar observations were made using the Alum /7DW8-5 combination. Examination of the impact of adjuvants on NKT cells revealed expansion of invariant NKT (iNKT) cells with modest expansion of their iNKTfh subset and little effect on diverse NKT (dNKT) cells. Side effects of the adjuvants was determined and revealed transient hepatotoxicity when Alum /α-GC was used in combination but not singly. In summary these results showed that the Alum /α-GC or the Alum /7DW8-5 combination could exert distinct effects on the NKT cell compartment and on isotype switch to produce Th1-driven IgG subclasses in addition to Alum /Th2-driven subclasses. While Alum alone was efficacious in stimulating IgG-mediated protection, and α-GC offered no apparent additional benefit in the C. difficile challenge model, the work herein reveals immune response features that could be optimized and harnessed in other vaccine contexts.